Implementation of Smart Onion Counting and Environmental Sensing System with ESP32 MCU - Suheta, Titiek; Suryowinoto, Andy; Uman, Novian Patria; Anam, Choirul (Universitas Nurul Jadid, 2025)
The rapid development of embedded system technology in recent decades has had a significant impact, this advancement has contributed to an increase in production capacity with real-time monitoring trough embedded system MCU ESP32. The process of manufacturing onion products, such as fried shallots and garlic. The objective of this research is to develop a low-cost automatic onion counting system that utilizes an embedded system MCU ESP32 with integration of infrared sensors, temperature and humidity sensors to monitor production quality conditions in real-time for small scale Industry. Using the engineering design method, where the TCRT5000 sensor is employed to detect objects based on infrared light interruption, and environmental conditions are measured with the DHT22 sensor to maintain production quality. The internet connection for wireless communication for transmitting data to a mobile device through google firebase. Analysis was performed to evaluate performance such as, data transmission response time, and environmental sensor precision. The results obtained demonstrate that the system attained counting accuracy rates of 98.2% for garlic and 98.55% for shallots. with average data transmission response times of 1.51 seconds and 1.89 seconds, respectively, achieving a success rate of 97.15%. The environmental monitoring sensors demonstrated a high degree of accuracy, with a margin of error of 0.18 °C for temperature and 0.3% for humidity. The results show that this system works effectively in automating onion counting and monitoring, with an accuracy rate of over 98% and a response time of less than 2 seconds, making it suitable for small-scale automated production.